Efeito do tratamento com progesterona sobre a reatividade vascular coronariana dependente do endotélio em ratas espontaneamente hipertensas - Costa, Debora Tacon da (2020)
Progesterone receptors are expressed in the endothelium and vascular smooth muscle and through them progesterone produces important effects such as the direct and indirect formation of vasoactive factors, essential for vascular homeostasis. Although relev